2019
DOI: 10.1037/rep0000272
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to perceived burden among caregivers of service members/veterans following TBI.

Abstract: To examine factors related to perceived caregiving burden in a sample of caregivers assisting service members and veterans (SMVs) across four areas: SMV injury and health status; caregiver life circumstances; caregiver duty and responsibilities; and caregiver needs. Research Method/Design: Participants were 214 caregivers (95.8% female; 86.0% spouse/partner; Age: M ϭ 38.6 years [SD ϭ 10.4]) of SMVs who sustained a mild, moderate, severe, or penetrating traumatic brain injury (TBI). Caregivers were recruited fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 68 publications
0
21
2
Order By: Relevance
“…The benefits of such an approach may have consequences beyond the individual. Reducing that additive burden may lessen the distress among family members caring for an SMV following TBI (Brickell et al., ). Treatment programs for TBIs, whether in the DoD, Veteran Affairs, or community programs, will have the most success with a holistic approach that attempts to address behavioral health concerns such as PTSD and helps individuals realize the important contribution of these factors in their overall health and functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of such an approach may have consequences beyond the individual. Reducing that additive burden may lessen the distress among family members caring for an SMV following TBI (Brickell et al., ). Treatment programs for TBIs, whether in the DoD, Veteran Affairs, or community programs, will have the most success with a holistic approach that attempts to address behavioral health concerns such as PTSD and helps individuals realize the important contribution of these factors in their overall health and functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers of people with brain injury have been found to have worse mental health compared with caregivers of people with dementia and caregivers of people with cancer (Harding et al, 2015). The uniqueness of caregiver stress for the caregivers of people with TBI is associated with the variance in the condition, the level of impairment, and the associated symptoms (Brickell et al, 2019). Severe TBIs, for example, are more likely to have a high impact on caregiver stress because the more severe the brain injury, the higher the chances that the person with TBI would experience long-term deficits in memory, attention, language, processing, and overall executive functioning (Manskow et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They also pointed out how they had lost control of their lives. Brickell et al found that caregivers of veterans who had suffered traumatic brain injury reported having less time to devote to themselves and their personal needs as well as to the needs of their other family members. A decrease in relationships and social interactions with family, friends, and neighbors was also noted as an outcome of caregiver demands adding to the stress of caretaking .…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…When that pattern is disrupted, whether through choice (such as getting married) or through circumstance (such as a debilitating illness), usual social interactions are often altered or curtailed. Brickell et al reported caregivers of patients with TBI who perceived their caregiving as being “high burden” devoted less time to themselves and their other children. In a study of caregiver burden, it was noted that caregivers of persons with schizophrenia reported having to give up their previous social life and stay in or near their house.…”
Section: Defining Attributes Antecedents Consequences and Exemplarsmentioning
confidence: 99%